Use of magnetic fields reduces α‐chaconine, α‐solanine, and total glycoalkaloids in stored potatoes (Solanum tuberosum L.) - Irungu, F.G.; Tanga, C.M.; Ndiritu, F.G.; Mwaura, L.; Moyo, M.; Mahungu, S.M. (Hindawi Limited, 2022)
This work aimed to assess the suitability of magnetic fields (MF) to reduce glycoalkaloids (GAs) in stored potatoes. The effects of the source of magnetic fields (direct current [DC] and alternating current [AC]), magnetic field intensity (1, 2, and 3 mT), and storage type (dark store-herein referred to as the control store and a commercial store with varying light intensity) on quantities of GAs were investigated. Subjecting tubers to increasing levels of MF intensities and placing them in the control store led to a significant (p < .05) decrease in alpha-chaconine and an increase in alpha-solanine. However, storage of potatoes in the commercial store after exposure to increasing MF intensities led to a significant (p < .05) decrease in alpha-solanine and an increase in alpha-chaconine. The use of AC MF with an intensity of 2 mT resulted in a significant (p < .05) reduction in alpha-chaconine, alpha-solanine, and TG. Novelty impact statement Magnetic fields are an emerging non-thermal technology that has wide potential in food processing applications. The findings in the current work revealed that magnetic fields can be used to reduce quantities of toxic glycoalkaloids in potatoes during storage, and thus improve their postharvest quality. The results offer practical insights on postharvest management of potatoes to ensure reduction of losses and thus positively impact food and nutritional security.